2020
DOI: 10.3390/microorganisms8010134
|View full text |Cite
|
Sign up to set email alerts
|

Doing More with Less: A Comparison of 16S Hypervariable Regions in Search of Defining the Shrimp Microbiota

Abstract: The shrimp has become the most valuable traded marine product in the world, and its microbiota plays an essential role in its development and overall health status. Massive high-throughput sequencing techniques using several hypervariable regions of the 16S rRNA gene are broadly applied in shrimp microbiota studies. However, it is essential to consider that the use of different hypervariable regions can influence the obtained data and the interpretation of the results. The present study compares the shrimp mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 62 publications
3
41
0
1
Order By: Relevance
“…The resolution of the V4 region of the 16S rRNA gene sequenced in this study could have influenced this outcome. García-López et al. (2020) have recently shown that both the V3 and V3V4 hypervariable regions capture a broader spectrum of microbiota diversity than the V4 region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resolution of the V4 region of the 16S rRNA gene sequenced in this study could have influenced this outcome. García-López et al. (2020) have recently shown that both the V3 and V3V4 hypervariable regions capture a broader spectrum of microbiota diversity than the V4 region.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) have recently shown that both the V3 and V3V4 hypervariable regions capture a broader spectrum of microbiota diversity than the V4 region. Although the V3 region offers the advantage of faster sequencing time and lower cost, the V3V4 region offers a higher taxonomic resolution at an increased cost ( García-López et al., 2020 ). Increased abundance of F irmicutes has been associated with increased nutrient absorption and energy harvest from diets ( Jumpertz et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic variations in the microbiota have been mainly explored using 16S rDNA profiling from environmental and aquaculture samples [ 4 , 6 , 7 ], frequently selecting up to two consecutive hypervariable regions [ 9 , 11 ]. A previous study determined that the hypervariable region V3 is a cost-effective alternative to determine the microbiota diversity in the shrimp hepatopancreas and the intestine [ 12 ]. Although amplicons spanning both the V3 and V4 regions bore a higher taxonomic resolution and diversity, the V3 region showed optimal family-level resolution and better performance than V4 at the genus level using current sequencing technologies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed a better taxonomic accuracy with the forward reads covering the V3 region of the 16S rRNA gene. Recent studies have shown that the V3 represents the best choice for the pro ling of complex microbial communities [25], for increased and more accurate estimates of community richness and diversity [26]. Thus, 270 bp reads covering V3 were used for downstream analyses, as in [25,26,27].…”
Section: Reads De-noising and Asv Identi Cationmentioning
confidence: 99%
“…Recent studies have shown that the V3 represents the best choice for the pro ling of complex microbial communities [25], for increased and more accurate estimates of community richness and diversity [26]. Thus, 270 bp reads covering V3 were used for downstream analyses, as in [25,26,27]. The standard dada2 pipeline was used, with a maximum of 2 expected errors (maxEE) and with default parameters as per version 1.14.1, except for the "dada" step where all samples were pooled for ASV inference [24].…”
Section: Reads De-noising and Asv Identi Cationmentioning
confidence: 99%